Contribution of waqf to the economic pillar for the sustainability of the tourism industry in Malaysia: an empirical investigation / Mohammed Izzuddin Ismail … [et al.] - Ismail, Mohammed Izzuddin; Ismail, Shafinar; Zahari, Mohd Salehuddin; Mohd Pauzi, Nur Farahah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Malaysia's tourism industry is the third-largest contributor to the country's economy. Aggressive measures have been taken to boost Malaysia as a leader in the tourism sector. Nevertheless, due to budget constraints the expected growth is not achievable. One of the options to overcome this constraint is to utilize waqf contributions. It is an innovative way to finance the tourism sector without totally relying on government funds. Therefore, the objective of this study is to investigate the contribution of waqf for long-term sustainability of the tourism industry in Malaysia. A quantitative approach is used through the distribution of questionnaires among 150 respondents which comprise of relevant parties in this industry. The purposive sampling procedure was adopted in this research. The results indicate that the contributions of waqf to the economic pillar have a significant relationship with the sustainability of the tourism industry. The analyses presented can be used by policymakers in regulating stimulus packages or incentives and relevant tourism policies for the local industry. The findings achieved in this research will be of interest to practitioners and academicians who are concerned with the sustainability of the tourism industry in Malaysia.